UWB Square Monopole Antenna with Omni-Directional Radiation Patterns for Use in Circular Cylindrical Microwave Imaging Systems - Ojaroudi, N.; Ojaroudi, M.; Ghadimi, N.; Mehranpour, M. (Applied Computational Electromagnetics Society Journal (ACES), 2021)
In this paper, a novel ultra-wideband printed monopole antenna (PMA) for the use in a circular cylindrical microwave imaging system is presented. The proposed antenna consists of a square radiating patch and a ground plane with a pair of L-shaped slots and two L-shaped conductor back plane, which provides a wide usable fractional bandwidth of more than 130 % (3.02 GHz - 15.21 GHz). By cutting two modified Lshaped slots with variable dimensions on the ground plane corners and also by inserting two Lshaped conductor back plane on the other side of the substrate, additional resonances are excited and hence much wider impedance bandwidth can be produced, especially at the higher band. The proposed antenna has an ordinary square radiating patch, therefore displays a good omni-directional radiation pattern even at higher frequencies, and also its radiation efficiency is greater than 82% across the entire radiating band. The designed antenna has a small size of 12 × 18 mm2. Simulated and measured results are presented to validate the usefulness of the proposed antenna structure for circular cylindrical microwave imaging system.